Fiji floriculture handbook - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2013)
More than one thousand people, mostly women, derive at least part of their livelihood from floriculture in Fiji. This handbook – prepared by SSO, the driving force behind the development of Fiji’s commercial floriculture industry – provides an overview of the industry. Aimed at growers, it looks to pass on the knowledge and skills necessary to start and maintain a small, viable floriculture business. Clearly and concisely laid out, with many colour photographs and diagrams detailing plant varieties, step-by-step processes for growing, harvesting and post-harvest handling, this wonderful resource serves as a handy and accessible reference. Later sections of the book address ‘Business basics’, such as developing a business plan, setting prices, marketing, and start up and operating costs. Many business aspects are dealt with separately as necessary for cut flowers, potted plants and trees, and for florists. With its final chapters detailing contacts, a useful glossary and references, this handbook outlines everything growers need to know to increase their income by producing more high-quality flowers and by making better use of inputs.